Production Of Gold And Silver Nanoparticles Recovered Through Sonication Of Reflective Metal Layer In Cd-R Waste - Ahmad, Azliyana (2013)
Reflective metal layer (gold and silver) in CD-R waste were separated by physical and chemical separation methods. Both types of reflective metal layer (gold and silver) were then sonicated in the ultrasonic units, Sonoswiss SW 12 H. The effect of three operating parameters during the sonication process were investigated, namely sonication features (degas, sweep and boost), sonication time and operating temperature. The product was then characterized by particle size analysis, Field Emission Scanning Electron Microscopy and Energy Dipersive Spectroscopy and Energy Filter Transmission Electron Microscopy and Electron Energy Loss Spectroscopy. It has been confirmed through the present study that the recycling process of CD-R waste can be carried out using simple methods such as physical and chemical separation using 0.5 M of acetone for gold and 0.5 M of HCL for silver. Production of fine gold nanoparticles was successfully done using sweep feature at high operating temperature range (55-65°C) at 10 min resulting in the minimum d50 at 1.01 nm and span value at 0.048. Similarly, production of fine silver nanoparticles was successfully done using boost feature at high operating temperature range (55-65°C) at 30 min resulting in the minimum d50 at 1.33 nm and span value at 0.281.